A Chemical-Based Pipeline Maintenance Decision Support System - Anyoku, W; Nwachukwu, EO; Eke, BO (International Journal of Computer Sciences and Engineering, 2020)
Pipeline Corrosion Management System is the process of analyzing corrosion status in a crude pipeline by extracting data from a Linear Polarization Resistance (Probe) to monitor corrosion behavior. Petroleum pipelines are prone to corrosion due to the sea water injection into the wells to increased pressure required to force crude from the reservoir. Petroleum pipelines maintenance therefore becomes very necessary so that imminent growth of bacteria and corrosion are eliminated. Many researchers has done tremendous work in detection and treatment corrosion caused mainly by microbial growth but these systems does not recommend appropriate chemicals and quantities for treatment of different types of corrosion discovered. Hence to solve these problems stated we develop a Chemical-Based Pipeline Maintenance Decision Support System. This system offers an online management technique which reads the Probe, extracts corrosion details and proffer chemical treatment if corrosion is found. An Object Oriented Analysis and Design (OOAD) methodology was adopted, while we used PHP programming language at the front end, and MySQL relational database at the backend to achieve this goal. Our findings reveal that corrosion inhibitors and biocides are good treatments for corrosion and bacteria growths in oil pipelines. The Linear Probe is faster for pipeline corrosion detection, treatment and recommendation when compared to the existing Coupon method. This system will give confidence to pipeline operator when handling corrosion detection and treatment and make them deliver their work timely and less expensive.